PRAGMATICS AND CONTEXTUAL FEATURES OF THE RELIGIOUS CONCEPTS FUNCTIONING IN INAUGURATION SPEECHES OF AMERICAN PRESIDENTS (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-41-53The article is devoted to the study of the semantic and contextual features of the inaugural speeches organization in cases when religious concepts function in them. The relevance of the study is determined by the importance of analyzing the pragmatic characteristics of the religious concepts functioning in American presidents’ inaugural speeches. Research methods are cognitive-discursive analysis, contextual analysis, method of quantitative processing of the material. Empirical material contains 57 inaugural texts, in which the functioning of religious concepts is noted in 296 contexts. US presidents regularly use religious concepts in their inaugural speeches, in some cases of their functioning, inaugural texts have certain structural features that are emphasized in this work. The article analyzes the main pragmatic guidelines for using these concepts: actualization of the moral and ethical values of society, underlining the importance of continuity in the history of the state, implication of the meaning of the divine election of the president and the idea of a special relationship of the Creator to the American people, seeking divine help in leading the state. The study of the role of the religious concepts functioning in the inaugural speeches of American presidents allows us to consider in more detail the linguistic and extralinguistic features of political discourse texts.Key words: religious concept, political discourse, inaugural text, pragmatics, implication